On-chip multivariant COVID 19 photonic sensor based on silicon nitride double-microring resonators - Grosman Arieh; Duanis-Assaf Tal; Mazurski Noa; Zektzer Roy; Frydendahl Christian; Stern Liron; Reches Meital; Levy Uriel (Nanophotonics)
Coronavirus disease 2019 (COVID-19) is a newly emerging human infectious disease that continues to develop new variants. A crucial step in the quest to reduce the infection is the development of rapid and reliable virus detectors. Here, we report a chip scale photonic sensing device consisting of a silicon-nitride double microring resonator (MRR) for detecting SARS-CoV-2 in clinical samples. The sensor is implemented by surface activation of one of the MRRs, acting as a probe, with DNA primers for SARS-CoV-2 RNA, whereas the other MRR is used as a reference. The performance of the sensor is determined by applying different amounts of SARS-CoV-2 complementary RNA. As will be shown in the paper, our device detects the RNA fragments at concentrations of 10 cp/μL and with sensitivity of 750 nm/RIU. As such, it shows a promise toward the implementation of label-free, small form factor, CMOS compatible biosensor for SARS-CoV-2, which is also environment, temperature, and pressure independent. Our approach can also be used for detecting other SARS-CoV-2 genes, as well as other viruses and pathogens.